Autoimmune Hepatitis: A Review of Current Diagnosis and Treatment. (17th April 2011) - Makol, Ashima; Watt, Kymberly D.; Chowdhary, Vaidehi R.
Abstract : Autoimmune hepatitis (AIH) is a chronic inflammatory disorder characterized by periportal inflammation, elevated immunoglobulins, autoantibodies, and a dramatic response to immunosuppression. An environmental agent is hypothesized to trigger an immune-mediated attack directed against liver antigens in genetically predisposed individuals. A plethora of clinical presentations can be seen ranging from chronic indolent disease to fulminant hepatic failure, and diagnosis requires exclusion of other causes of liver disease. Corticosteroid therapy must be instituted early and modified in an individualized fashion. Treatment decisions are often complicated by the diverse clinical manifestations, uncertainty about natural history, evolving ideas about treatment end points, and a multitude of alternative immunosuppressive agents. Achieving normal liver tests and tissue is the ideal treatment end point, but needs to be weighed against the risk of side effects. Decompensated patients may benefit from early liver transplantation. Long-term prognosis is excellent with early and aggressive initiation of therapy. Our paper discusses AIH, giving a detailed overview of its clinical presentation, risk factors, immunopathogenesis, up-to-date diagnostic criteria, current updates in therapy with a brief discussion of AIH in pregnancy, and long-term implications for cirrhosis and hepatocellular carcinoma in AIH patients.